Characterization and thermal degradation of poly(2-methacrylamidopyridine) - Coskun, M; Temüz, MM; Demirelli, K (Elsevier Sci Ltd, 2002)
2-Methacrylamidopyridine (MAPy) was prepared by reaction of methacryloyl chloride with 2-aminopyridine. The MAPy was polymerized in the presence of 2,2'azobisisobutyronitrile (AlBN) as an initiator in acetonitrile. The thermal decomposition behaviour of poly(2-methacrylamidopyridine) [poly(MAPy)] was investigated by thermogravimetric analysis (TG) and by programmed heating of the polymer from ambient temperature to 300, then from 300 to 500 degreesC under vacuum, and was followed by product collection, and by using IR spectra of partially degraded polymer. The products volatile at degradation temperature but not at ambient temperature were separately collected, after each heating, stage on the cooled upper part of the degradation tube (cold ring fraction, CRF1 for between ambient temperature and 300 degreesC, CRF2 for between 300 and 500 degreesC). The H-1-NMR spectrum showed that almost all of the light yellow coloured CRF1 is 2-aminopyridine, not including some very small signals. On the other hand, the CRF2 showed that 2-aminopyridine and 2-methacrylamidopyridine formed as main products. The activation energy of thermal degradation of poly(MAPy), in the first stage of decomposition, was calculated as 110 kJ mol(-1), and the pre-exponential factor as 5.42 x 10(11) s(-1). The mechanism of thermal degradation including formation of the major products is discussed. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: methacrylamidopyridine; thermal degradation